Assessment of PD-L1 mRNA expression in gastrointestinal tumors and the response to immunotherapy - Qiu, Qingqing; Li, Jieyi; Chen, Qiaofeng; Zhao, Xiaokai; Zhou, Ru; Zhang, Wenpeng; Gong, Ziying; Zhang, Daoyun; Wang, Mingliang (Frontiers in Oncology, 2022)
Background Programmed death ligand 1 (PD-L1) immunohistochemistry (IHC) has been proposed as a predictive biomarker to predict response to immunotherapy. Given the limitations of IHC test in PD-L1 detection, this study aimed to investigate the technical feasibility of using quantitative RT-PCR (qRT-PCR) to replace IHC in PD-L1 detection in gastrointestinal tumors. Materials and methods The Cancer Genome Atlas database was used to evaluate the relationship between PD-L1 expression in tumor tissue and the patient prognosis. In addition, 52 patients with gastrointestinal cancer were enrolled and divided into the stomach (STAD), colon (COAD), and rectum (READ) adenocarcinoma cohorts. IHC test was used to determine the PD-L1 level of the tissue specimens, and the qRT-PCR test was used to analyze the mRNA expression in both blood and tissue specimens. Moreover, the correlation between blood PD-L1 mRNA expression and immunotherapy efficacy was investigated in additional 15 patients with gastric cancer that further enrolled. Results The expression level of PD-L1 in tumor tissue is related to the tumor stage of COAD (p-value = 0.001) and primary therapy outcomes in patients with READ (p-value = 0.003) but not significantly correlated to the overall survival (OS) time of patients with gastrointestinal cancer. Moreover, the concordance of PD-L1 mRNA expression level of tissue and paired blood samples is low, despite a weak linear relationship that was found in the STAD cohort (r = 0.43, p-value = 0.049). We further demonstrated that qRT-PCR results in both tissue and blood specimens were numerically but not statistically significant consistent with IHC results (corresponding to a p-value of 0.84 and 0.55, respectively). Remarkably, high PD-L1 expression in blood of patients with STAD shows a better response to immunotherapy (p-value = 0.04), which could be well identified at the relative expression cutoff of 1.5 (sensitivity of 85.7%, specificity of 75.0%, and AUC of 0.82). Conclusions Our study established a novel strategy for rapidly distinguishing patients with gastrointestinal cancer with the response to immunotherapy and has potential clinical benefits.